RASIONALITAS DAKWAH SUNAN BONANG - Jauharotina Alfadhilah; Jamal Ghofir (Program Studi Manajemen Dakwah, Fakultas Dakwah, Institut Agama Islam Nahdlatul Ulama Tuban, 2023)
Javanese Hindu traditions have been ingrained in the majority or even almost all circles of the people of the archipelago, especially the island of Java at the beginning of the spread of Islam in the archipelago. The condition of the community that is very close to the acculturation of local culture makes Sunan Bonang think hard to use his rationality in efforts to spread Islam. Rational which means a mindset where someone tends to behave and act based on logic and human reason, making Sunan Bonang, who is more often known as Maulana Makhdum Ibrahim, argues that Islamic teachings delivered and preached by force will not be able to flow Islamic breath in the souls of the community. Witing Tresno Jalaran soko kulino (love grows due to frequent interactions). If Islam can be well interacted with society, then gradually without realizing it, Islam can be in their hearts without violence and coercion. Islam is a religion that exists with peace, no coercion let alone violence as described in Q.S. Al-Baqarah 256. Therefore, cultural acculturation by incorporating Islamic breath in every culture and activity carried out by the community is clear evidence of the rationality of Sunan Bonang's thoughts in choosing the right da'wah strategy to be able to introduce Islam to the people of Java and Nusantara which at that time was very thick with its traditions.